2019
DOI: 10.3390/su11020387
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of a Sustainability Awareness Indicator in Assessment Tools for High School Buildings

Abstract: The growing debate about global environmental problems is evident in several spheres of society. The concern for the future of the planet is used as a political slogan, inspiring the creation of new laws and encouraging academic research that serves this purpose, as well as increasing the number of government agencies concerned with this matter. The 21st century is considered the "century of sustainable development". Sustainability education in high schools has the potential to make the benefits of civil const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…It must be noted that, although the standards of construction and reform are established by the EPE, to know the result achieved by each particular school, the global methodology [14,22] must be applied to each school, which includes the application of the questionnaires to the students, the measurement of key indicators and the consultation of the school management reports, taking also into account the climate context, the type of construction as well as the urban context. These results demonstrated that more than 82% of the categories achieved a level of at least category B, demonstrating that the Empresa Parque Escolar is achieving its objectives related to the habitability and environmental comfort conditions (air and thermic quality) and accessibility, to modernize equipment and safety, besides guaranteeing energy efficiency and the flexibility and adaptability of the school buildings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that, although the standards of construction and reform are established by the EPE, to know the result achieved by each particular school, the global methodology [14,22] must be applied to each school, which includes the application of the questionnaires to the students, the measurement of key indicators and the consultation of the school management reports, taking also into account the climate context, the type of construction as well as the urban context. These results demonstrated that more than 82% of the categories achieved a level of at least category B, demonstrating that the Empresa Parque Escolar is achieving its objectives related to the habitability and environmental comfort conditions (air and thermic quality) and accessibility, to modernize equipment and safety, besides guaranteeing energy efficiency and the flexibility and adaptability of the school buildings.…”
Section: Discussionmentioning
confidence: 99%
“…Energy efficiency is one of the major objectives of the Empresa Parque Escolar, seeking to "ensure the energy efficiency of buildings in order to reduce operating costs" [21]. According to the Regulatory Compliance Statement [14] of this school building, the total amount spent on energy is 18.61 Kgp/m 2 -year.…”
Section: Value [A] × [B] =mentioning
confidence: 99%
“…Other issues addressed are environmental practices in students' homes and how students believe environmental issues should be addressed in high schools. This indicator encourages awareness of sustainability among students and promotes positive attitudes towards sustainability in the students' daily lives [24]. This is a new indicator developed for the SAHSB PT methodology.…”
Section: Indicator 21-sustainability Awarenessmentioning
confidence: 99%
“…Ante la serie de incertidumbres generadas por la pandemia del COVID-19, el proceso de construcción de alternativas para hacer que el siglo XXI se encamine hacia la sustentabilidad (Saraiva et al, 2019) se ha visto complicado, más no cancelado. La coyuntura de la pandemia y de la "nueva normalidad" que se deriva de ésta (Pinazo-Hernandis, 2020), ha representado la complicación y reactualización de viejos problemas sociales tanto de índole ecológica, económica, sanitaria y política.…”
Section: Introductionunclassified